2020
DOI: 10.1002/anie.202002516
|View full text |Cite
|
Sign up to set email alerts
|

A Photoinduced Nonadiabatic Decay‐Guided Molecular Motor Triggers Effective Photothermal Conversion for Cancer Therapy

Abstract: It remains highly challenging to identify small molecule‐based photothermal agents with a high photothermal conversion efficiency (PTCE). Herein, we adopt a double bond‐based molecular motor concept to develop a new class of small photothermal agents to break the current design bottleneck. As the double‐bond is twisted by strong twisted intramolecular charge transfer (TICT) upon irradiation, the excited agents can deactivate non‐radiatively through the conical intersection (CI) of internal conversion, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 47 publications
4
69
1
Order By: Relevance
“…In order to augment PA effect, scientists have advanced the nonradiative decay efficiency [15] of photothermal agents besides their absorption coefficient [10b,16] and Grüneisen parameter. [17] Such agents based on intramolecular motion-induced photothermy, [15a] molecular motion in aggregates, [15b] or photoinduced nonadiabatic decay [18] have thus been intensively developed. However,s of ar,t he strategic guidance for constructing high-efficient PA agents is still very rare.T hus, giving new insight into how to efficiently convert the absorbed light energy into heat and further elaborating the design mechanism and principle of PA agents with high nonradiative decay efficiency will further put forward the potential biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to augment PA effect, scientists have advanced the nonradiative decay efficiency [15] of photothermal agents besides their absorption coefficient [10b,16] and Grüneisen parameter. [17] Such agents based on intramolecular motion-induced photothermy, [15a] molecular motion in aggregates, [15b] or photoinduced nonadiabatic decay [18] have thus been intensively developed. However,s of ar,t he strategic guidance for constructing high-efficient PA agents is still very rare.T hus, giving new insight into how to efficiently convert the absorbed light energy into heat and further elaborating the design mechanism and principle of PA agents with high nonradiative decay efficiency will further put forward the potential biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…To study the relationship between ROS generation of AIEgens and their capacity to trigger macrophage polarization, tTDCR, tTID,and tTBCI were encapsulated by an amphiphilic polymer to afford waterdispersible nanoparticles (NPs) following our established protocols. [12] TheN Ps have average hydrodynamic diameters of 20-30 nm in water ( Figure S16). Their photophysical properties have been included in the supporting information (Figures S17-S19, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo experiments (Figures 5(F) and 5(G)) indicated that the new agent served as an efficient probe for PA imaging and PT ablation of tumor under safe NIR laser irradiation (0.3 W cm −2 , 808 nm). Recently, Li's group adopted a double bond–based molecular motor concept to develop highly efficient PT agents 168 . They synthesized an imino‐based molecular motor that induced easier intramolecular motions through the double‐bond torsion‐causing photoinduced nonadiabatic decay effect.…”
Section: Pa Imaging and Pttmentioning
confidence: 99%
“…Copyright 2020 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim. (H–I) Reproduced with permission 168 . Copyright 2020 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim…”
Section: Pa Imaging and Pttmentioning
confidence: 99%